The Same God Question in the context of oppression - Willoughby, J. David (Missiology, 2025)
In recent years, the ongoing debate regarding whether Muslims and Christians worship the same God has predominantly been discussed from theological and philosophical perspectives. Yet, a significant gap exists in exploring this discourse through a sociological lens, particularly in understanding how the “Same God Question” resonates within the contexts of minority groups and the oppressed. This article addresses this gap by investigating the viewpoints of those often marginalized in discussions of religious identity. Drawing upon Henning Wrogemann’s observations on the complex interplay between contextualization to those in positions of influence versus the rights of the oppressed, as well as Robert Priest’s insights on experience-near theology, this article argues that it is possible for contextualization to one group to unwittingly perpetuate oppression to another group. Furthermore, it asserts the fundamental right of oppressed individuals to distance themselves from the overarching theological frameworks imposed upon them by hegemonic forces. These insights are subsequently applied to the broader discourse surrounding the “Same God Question” in order to highlight the complex interplay between contextualization, power, and oppression.